Zionism and anti-semitism in Nazi Germany - Nicosia, Francis R. (Cambridge University Press, 2008)
The age of emancipation in imperial Germany -- The Weimar years -- 1933 : Nazi confusion, Zionist illusion -- Zionism in Nazi Jewish policy, 1934-1938 -- German Zionism, 1934-1938 : confrontation with reality -- Revisionist Zionism in Germany, 1934-1938 -- Occupational retraining and Nazi Jewish policy -- From dissolution to final solution